Implementation of Instructor Teaching Method to Promote Active Participation of Computer Training Participants - Zedra Yuhendika; Jamaris Jamna (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research is motivated by the success of the participants in achieving the goal of developing knowledge and skills about computers.  The existence of the Putri Gumanti Community Learning Activity Center (PKBM) through computer training programs helps to realize the wishes of participants in achieving the program implementation goals provided by the institution.  The research approach is qualitative, with the type of case study research.  Sources of data in this study consisted of training participants as subjects, and instructors and managers as informants.  Data collection techniques used are interviews, observation and documentation.  Data analysis techniques used are data reduction, data presentation, and drawing conclusions.  The data validity technique uses source triangulation and method triangulation.  The results of this study indicate that: (1) The trainees are active and enthusiastic in listening to the instructor in delivering the material;  (2) The instructor provides space for participants to ask questions, have opinions, discuss and work together in the learning process, the effort is made so that the participants are active in participating in the training;  (3) In carrying out the practice the participants help each other if someone is having difficulties;  (4) The use of varied methods is considered very effective in the implementation of the training so that participants do not get bored easily.